Host–pathogen coevolution in the presence of predators: fluctuating selection and ecological feedbacks - Best, Alex (Proc Biol Sci, 2018)
Host–pathogen coevolution is central to shaping natural communities and is the focus of much experimental and theoretical study. For tractability, the vast majority of studies assume the host and pathogen interact in isolation, yet in reality, they will form one part of complex communities, with predation likely to be a particularly key interaction. Here, I present, to my knowledge, the first theoretical study to assess the impact of predation on the coevolution of costly host resistance and pathogen transmission. I show that fluctuating selection is most likely when predators selectively prey upon infected hosts, but that saturating predation, owing to large handling times, dramatically restricts the potential for fluctuations. I also show how host evolution may drive either enemy to extinction, and demonstrate that while predation selects for low host resistance and high pathogen infectivity, ecological feedbacks mean this results in lower infection rates when predators are present. I emphasize the importance of accounting for varying population sizes, and place the models in the context of recent experimental studies.